From Leaders, For Leaders: Advice From the Lived Experience of Leaders in Community Health Sector Disaster Recovery After Hurricanes Irene and Sandy. (20th June 2016) - Craddock, Hillary A.; Walsh, Lauren; Strauss-Riggs, Kandra; Schor, Kenneth
Abstract: Objective: Hurricanes Sandy and Irene damaged and destroyed homes, businesses, and infrastructure, and recovery after these storms took years. The goal of this article was to learn from the lived experience of local-level decision-makers actively involved in the long-term disaster recovery process after Hurricanes Irene and Sandy. Respondents provided professional recommendations, based on their experience, to assist other organizations in preparing for, responding to, and recovering from disasters. Methods: Semi-structured interviews were conducted with professionals actively involved in recovery from Hurricane Irene or Hurricane Sandy in 5 different communities. Transcripts were qualitatively analyzed. Results: Respondents' advice fell into 5 main categories: planning and evaluation, education and training, fundraising and donations management, building relationships, and disaster behavioral health. Conclusions: The lived experience of those in disaster recovery can provide guidance for planning, education, and training both within and outside their communities in order to better respond to and recover from future disasters. These data help to facilitate a community of practice by compiling and sharing the lived experience of leaders who experienced large-scale disasters, and the outcomes of this analysis help to show what areas of planning require special attention in the phases of preparedness, response, and recovery. ( Disaster Med Public Health Preparedness . 2016;10:623–630)